2005
DOI: 10.1158/0008-5472.can-05-0404
|View full text |Cite
|
Sign up to set email alerts
|

Poor Survival Associated with the BRAF V600E Mutation in Microsatellite-Stable Colon Cancers

Abstract: The BRAF V600E mutation has been associated with microsatellite instability and the CpG island methylator phenotype (CIMP) in colon cancer. We evaluated a large populationbased sample of individuals with colon cancer to determine its relationship to survival and other clinicopathologic variables. The V600E BRAF mutation was seen in 5% (40 of 803) of microsatellite-stable tumors and 51.8% (43 of 83) of microsatellite-unstable tumors. In microsatellite-stable tumors, this mutation was related to poor survival, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

62
559
19
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 689 publications
(662 citation statements)
references
References 15 publications
62
559
19
14
Order By: Relevance
“…Several studies have shown that BRAF V600E mutation does not affect prognosis in colorectal cancers with high-level microsatellite instability, but adversely affects survival in microsatellitestable colorectal cancers. [31][32][33][34] This phenomenon was also observed in signet ring cell carcinoma in this series with 43% 5-year survival in microsatellitestable cases lacking BRAF V600E mutation compared with none among tumors with the mutation.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Several studies have shown that BRAF V600E mutation does not affect prognosis in colorectal cancers with high-level microsatellite instability, but adversely affects survival in microsatellitestable colorectal cancers. [31][32][33][34] This phenomenon was also observed in signet ring cell carcinoma in this series with 43% 5-year survival in microsatellitestable cases lacking BRAF V600E mutation compared with none among tumors with the mutation.…”
Section: Discussionsupporting
confidence: 56%
“…BRAF V600E mutation occurs in 34-80% of cancers with high level of microsatellite instability and 5-15% of microsatellite-stable cancers. [31][32][33][34] BRAF V600E mutation has been associated with poor survival in patients with microsatellite-stable, but not microsatellite-unstable, colorectal cancers. [31][32][33][34] In fact, BRAF V600E mutation does not adversely affect the favorable survival associated with tumors that show high level of microsatellite instability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the presence of B-raf mutations in colorectal cancer is estimated to be about 10% of unselected colorectal cancers [42-44]. In particular, B-raf T1799A mutation (V600E) has been reported in 4% of microsatellite stable (MSS) tumors whereas in microsatellite unstable tumors the percentage rises up to 27-52% [42,44-46]. By analogy to those investigations we detected V600E B-raf mutations in about 7% of MSS tumors and in 21% of MSI unstable tumors.…”
Section: Discussionmentioning
confidence: 99%